Community understanding, perceptions, and involvement in tourism development in King Nehale constituency, Namibia (Journal for Studies in Humanities and Social Sciences, 2019)
Tourism is one of the rapidly growing industries in the world. The development of this sector has become a strategy for poverty alleviation and economic development for developed and developing countries. Community contributions and knowledge of tourism play a significant role in the development of tourism. This paper assesses community understanding and perceptions of tourism development in the King Nehale Conservancy. The study used both interviews guides and semi-structured questionnaires for data collection. Microsoft Excel was used to analyse quantitative data, while qualitative data was analysed thematically. The findings suggest that local people in the King Nehale Conservancy do not understand tourism development. Majority of the respondents are not involved in tourism activities except those who are in the conservancy and thus have negative perceptions of tourism development. Craft making/selling was found to be the essential tourism-related activity of the conservancy.